Quantum Leaps for Deaf Studies in Ireland - LEESON, LORRAINE (My University, 2009)
The Centre for Deaf Studies, Trinity College Dublin, is delighted to announce the launch of a NEW four year Bachelor in Deaf Studies Programme. This full-time programme leads to a level 8 qualification in the National Framework of Qualifications and is accredited by Trinity College Dublin. Years 1 and 2 of the programme offer a solid basis in Deaf Studies and language studies. Students take some courses alongside students from across the College as part of the Broad Curriculum as well as core courses in Irish Sign Language over the four years of the degree. The programme leads to specialist options in ISL/English interpreting, ISL teaching or Deaf Studies in years 3 and 4 of the degree. This degree programme brings Ireland in line with best practice internationally and we are delighted to offer students in the last two years of the programme the option of studying abroad with one of our Erasmus partners, for example, the Humak Institute in Finland.
IN_PRESS
Keywords: CLCS